ANALISIS RETORIKA DAN PROPAGANDA ANIES BASWEDAN: EDISI KE-3 TAHUN 2024 - Ratih Saspira; Yusnita , Titien; Muslikhah , Febri Palupi (JURNAL SAHID DA'WATII, 2025)
Ahead of the general election, the third edition of the debate between presidential candidate Anies Baswedan. This debate is related to the work program that will be carried out after being elected as president of the Republic of Indonesia. The third edition of the debate with the theme "Defense, Security, Geopolitics, and International Relations" has one of the debates that invites pros and cons. The audience feels empathy with the debate because of that. The micro, macro, and superstructure structures surrounding the debate between presidential candidate Anies Baswedan are revealed in this study. This descriptive qualitative study uses the Teun A. van Dijk model method. Data were taken from discussions in the debate. The results of the study indicate that advertisements have micro, macro, and superstructure components.